Establishment of Methylation-Specific PCR for the Mouse p53 Gene. (12th December 2011) - Okazaki, Ryuji; Ootsuyama, Akira; Yoshida, Yasuhiro; Norimura, Toshiyuki
Abstract : Methylation-specific PCR (MSP) of the mouse p53 gene has not yet been reported. We searched the CpG islands, sequenced the bisulfited DNA, and designed PCR primers for methylation and unmethylation sites. DNA from a young mouse produced a strong PCR product with the unmethylated primer and a weaker band with the methylated primer. DNA from an old mouse produced bands of similar intensities with both primers. In radiation-induced tumors, DNA from an old mouse yielded similar bands with both types of primers. We suggest that MSP is a valuable technique for the epigenetic study of the mouse p53 gene.